2007
DOI: 10.1163/156855307782227417
|View full text |Cite
|
Sign up to set email alerts
|

A 10-gram vision-based flying robot

Abstract: We aim at developing ultralight autonomous microflyers capable of freely flying within houses or small built environments while avoiding collisions. Our latest prototype is a fixed-wing aircraft weighing a mere 10 g, flying around 1.5 m/s and carrying the necessary electronics for airspeed regulation and lateral collision avoidance. This microflyer is equipped with two tiny camera modules, two rate gyroscopes, an anemometer, a small microcontroller, and a Bluetooth radio module. Inflight tests are carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 24 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…The addition of lateral optic flow sensors also allowed a fixed-wing drone to detect near-ground obstacles 55 . Optic flow has also been used to perform both collision-free navigation and altitude control of indoor 56 and outdoor 57 fixed-wing drones without a GPS. In these drones, the roll angle was regulated by optic flow in the horizontal direction and the pitch angle was regulated by optic flow in the vertical direction, while the ground speed was measured and maintained by wind-speed sensors.…”
Section: Review Insightmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of lateral optic flow sensors also allowed a fixed-wing drone to detect near-ground obstacles 55 . Optic flow has also been used to perform both collision-free navigation and altitude control of indoor 56 and outdoor 57 fixed-wing drones without a GPS. In these drones, the roll angle was regulated by optic flow in the horizontal direction and the pitch angle was regulated by optic flow in the vertical direction, while the ground speed was measured and maintained by wind-speed sensors.…”
Section: Review Insightmentioning
confidence: 99%
“…For example, some authors [55][56][57] have resorted to using the multiple optic flow sensors found in computer optical mice. Whereas others 68,69 have developed neuromorphic chips that not only extract optic flow, but also adapt to the large variety of light intensities that can be experienced when flying in confined spaces.…”
Section: Review Insightmentioning
confidence: 99%
“…They, became smaller and lighter than their predecessors, reaching true points of excellence. Consider, for example, the MC2 EPFL, a 5-gram fixed wing aircraft made of carbon fibers and thin films Mylar [6] [7] or MicroGlider developed by Wood and colleagues [8].…”
Section: Unmanned Aerial Vehicle (Uav): General Presentationmentioning
confidence: 99%
“…The on-board actuators and electronics consists of (a) a 4 mm geared motor with a lightweight carbon-fiber propeller, (b) two magnet-in-a-coil actuators controlling the rudder and the elevator, (c) a microcontroller board with a Bluetooth wireless communication module and a ventral camera with its pitch rate gyro, (d) a front camera with its yaw rate gyro, (e) an anemometer, and (f) a 65 mAh lithium-polymer battery. Reprinted from [25]. The anemometer is compared to a given setpoint to output a signal that is used to proportionally drive the engine in order to maintain airspeed reasonably constant.…”
Section: Vision-based Flightmentioning
confidence: 99%